2003
DOI: 10.1016/s1074-7613(03)00116-x
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Specific CD8 T Cells in Peripheral Tissues Are More Resistant to Apoptosis Than Those in Lymphoid Organs

Abstract: CD8 T cells persist at high frequencies in peripheral organs after resolution of an immune response, and their presence in the periphery is important for resistance to secondary challenge. We show here that LCMV-specific T cells in peripheral tissue (peritoneal cavity, lung, fat pads) reacted much less with the apoptotic marker Annexin-V than those in spleen and lymph nodes. This was not due to a TCR-based selection. In comparison to lymphoid tissue, T cells in the periphery expressed lower levels of Fas and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
82
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 49 publications
12
82
0
Order By: Relevance
“…TUNEL is also limited as it measures end-stage apoptosis. Indicative of these limitations, high annexin ϩ , but low TUNEL ϩ cell frequencies were recorded for the spleen of lymphocytic choriomeningitis-infected mice (34), presumably due to effective clearance of late apoptotic cells. This increased apoptosis of cells from the spleen and MLN (34), as compared with peripheral tissues, is consistent with the present findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TUNEL is also limited as it measures end-stage apoptosis. Indicative of these limitations, high annexin ϩ , but low TUNEL ϩ cell frequencies were recorded for the spleen of lymphocytic choriomeningitis-infected mice (34), presumably due to effective clearance of late apoptotic cells. This increased apoptosis of cells from the spleen and MLN (34), as compared with peripheral tissues, is consistent with the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study reported increased apoptosis and impaired function of liver CD8 ϩ T cells specific for influenza in a nontransgenic mouse model (36). By contrast, Wang et al (34) and others (37) reported high concentration of apoptotic LCMV-specific CD8 ϩ T cells in the responding lymphoid tissue. Moreover, livers of mice infected with Listeria monocytogenes (LM) (38), lymphocytic choriomeningitis (39), and vesicular stomatitis virus (40) were highly enriched for functionally competent Ag-specific CD8 ϩ T cells (38).…”
Section: Irus Infections Induce the Expansion And Differentiationmentioning
confidence: 98%
See 1 more Smart Citation
“…To confirm that staining with fluorogenic caspase substrates was a valid indicator of programming for apoptosis, we adopted the method of TUNEL staining ex vivo after a brief period of culture (26). Fig.…”
Section: Caspase Activation Correlates With Apoptosis Assessed By Tunelmentioning
confidence: 99%
“…95 This could be of particular interest in HIV infection where high viral load is present in lymph nodes during the onset of the infection. 96 However, studies in mouse viral models have revealed a differential tissue-specific regulation of virusspecific CD8 þ T cells, 95,97,98 underscoring the difficulty of a comprehensive analysis of the in vivo regulation of the HIVspecific CD8 þ T-cell response. Overall, persistent exposure of HIV-specific CD8 þ T cells to their targets could result in selective sensitization of these cells.…”
Section: Chronic Activation Of the Immune Systemmentioning
confidence: 99%